Оценка наследования срока созревания плодов в гибридном потомстве Persic vulgaris Mill. - Лацко, Т.А. (Фактори експериментальної еволюції організмів, 2013)
Aims. It is believed that the fruit ripening period peach Persica vulgaris mill. controlled by polygenes and is inherited by the type of quantitative traits. The available data are different and contradictory. The goal was to trace the inheritance of fruit ripening period in the first and second generation of hybrid peach. The question is of practical and theoretical importance. Methods. Hybridization and selection study performed by the program and the methods of selection and study of varieties of fruit, berry and nut crops, developed Michurinsk (1974, 1980). Assessment of 20 crossing combinations hybrid families held in the southern steppe agro-climatic zone of Ukraine. Results. The analysis of the offspring (first and second F1 F2 generations) on the term of fruit ripening revealed four types of hybrid seedlings segregating normal, skewed, bimodal and erratic. Conclusions. This segregating of the peach hybrid progenies on deadline the fruit ripening period proves confirms not only polygenic, but oligogene control of this trait.